2012
DOI: 10.1111/j.1460-9592.2012.03883.x
|View full text |Cite
|
Sign up to set email alerts
|

The EEG signal: a window on the cortical brain activity

Abstract: The accurate assessment of the depth of anesthesia, allowing a more accurate adaptation of the doses of hypnotics, is an important end point for the anesthesiologist. It is a particularly crucial issue in pediatric anesthesia, in the context of the recent controversies about the potential neurological consequences of the main anesthetic drugs on the developing brain. The electroencephalogram signal reflects the electrical activity of the neurons in the cerebral cortex. It is thus the key to assessment of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 56 publications
5
69
0
2
Order By: Relevance
“…The rationale for the division of oscillations enables detailed interpretation of the brain regions being activated and how they are altered by analgesics . A schematic illustration of the generation of oscillations is given in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for the division of oscillations enables detailed interpretation of the brain regions being activated and how they are altered by analgesics . A schematic illustration of the generation of oscillations is given in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…The electroencephalogram (EEG) is the graphic registry of the electrical activity of the brain . It is based on a mathematical process called the fast Fourier transform (FFT), which separates a complex sinusoidal wave into a sum of simple wave forms of specific frequency and voltage . Thus, brain rhythms can be used as biomarkers of physiological and pathological states of rest and activity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Schlereth et al [28] found a left-hemisphere dominance in early sensory-discriminative dimensions of nociceptive pain processing (particular in left frontal operculum and adjacent dorsal insula). However, most studies have been conducted with higher doses, and it has been postulated that opioids only affect the EEG in high doses [29]. In this study, remifentanil induced alterations even after a low dose of remifentanil.…”
Section: Clinical Correlations Of the Eegmentioning
confidence: 67%